Benzoxazine resin containing acenaphthene ring structure and composition for copper-clad plate

By introducing acetonitrile structure and other resins into benzoxazine resin, the existing benzoxazine resin has been solved, and the production demand for high-performance copper clad plates is achieved.

CN119875295APending Publication Date: 2025-04-25JIANGSU EMT NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510090600.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing benzoxazine resins are insufficient in high-frequency and high-speed copper clad plate applications, and are difficult to meet the needs of high-performance copper clad plates.

Method used

By introducing an acetocyclic structure, acetocyclic compound and a double bond-containing phenolic compound are used to undergo radical polymerization reaction to form an olpolymer containing phenolic hydroxyl groups, and react with paraformaldehyde and amine compounds to prepare a benzoxazine resin containing an acetocyclic structure. At the same time, DCPD epoxy resin and maleimide resin are added to form a copper clad composition.

Benefits of technology

The heat resistance and glass transition temperature of the resin are improved, and the dielectric constant and dielectric loss are reduced, making the composition suitable for the production of high-frequency and high-speed copper clad plates, with the characteristics of high peel strength, low dielectric constant and low dielectric loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_6
    Figure SMS_6
  • Figure SMS_13
    Figure SMS_13
  • Figure SMS_15
    Figure SMS_15
Patent Text Reader

Abstract

The invention relates to benzoxazine resin containing an acenaphthene ring structure and a composition for a copper-clad plate. The composition is prepared by uniformly mixing and stirring 50 parts by mass of benzoxazine resin containing an acenaphthene ring structure, 20-30 parts by mass of DCPD epoxy resin, 10-20 parts by mass of maleimide resin, 0.1-0.5 part by mass of an imidazole catalyst, 60-80 parts by mass of a filler and 60-100 parts by mass of a solvent II at the temperature of 30-50 DEG C. According to the benzoxazine resin containing the acenaphthene ring structure, a phenolic compound containing double bonds and an acenaphthene compound are subjected to a free radical polymerization reaction, an oligomer containing phenolic hydroxyl groups is generated, then the oligomer reacts with paraformaldehyde and an amine compound, and then the acenaphthene ring structure can be introduced into the benzoxazine resin. By introducing an acenaphthene ring, the free volume of the benzoxazine resin is increased, and the dielectric constant and dielectric loss of the resin are reduced; meanwhile, the heat resistance of the product is improved by utilizing a biphenyl structure in an acenaphthene ring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of copper clad laminate preparation, and in particular to a benzoxazine resin containing an acenaphthene ring structure and a composition for copper clad laminates. Background Art

[0002] With the rapid development of artificial intelligence, 5G communications, and smart driving, new requirements have been put forward for PCB substrates and base resins, which are important components of electronic products, requiring them to have higher heat resistance, better dielectric properties, etc. Conventional benzoxazine resins such as bisphenol A and bisphenol F are only suitable for the pressing of ordinary copper clad laminates due to their poor heat resistance and slightly poor dielectric properties. They cannot be used on high-frequency and high-speed copper clad laminates. Therefore, people try to further develop and synthesize benzoxazine with high heat resistance, low dielectric constant, and low dielectric loss.

[0003] In order to improve the heat resistance of benzoxazine resin and reduce the dielectric constant and dielectric loss, CN103936686A discloses "N-semiaromatic hydrocarbon diamine-bisphenol type tetrafunctional fluorenyl benzoxazine and preparation method", first synthesizing a precursor containing both phenolic hydroxyl and amino groups, and then reacting it with polyformaldehyde and fatty amine to form a multifunctional benzoxazine resin containing fluorenyl groups, the resin glass transition temperature (Tg) is greater than 300 ° C; CN113896850A discloses "a flame retardant, high heat resistance and low dielectric benzoxazine resin", which is a benzoxazine containing an alkynyl group and an amide monomer containing an alkynyl group. The reaction forms a benzoxazine resin containing an imine structure, and the resin has a thermal weight loss temperature (Td5%) of >395°C and a Dk (10GHz) of <3.25; CN116606410A discloses "a large free volume and high heat-resistant benzoxazine resin", which is prepared by the reaction of hordenine with hexamethylenediamine or decanediamine, and the resin has a Tg of 233°C and a Dk (1MHz) of 2.56; CN107522831A discloses "a novel high-temperature resistant and low-dielectric silicon-containing benzoxazine and its preparation method", and a silicon group is introduced into the benzoxazine structure, and the resin Tg can reach 319°C. However, in the reported materials, there are few reports on methods of improving heat resistance, reducing dielectric constant and dielectric loss by introducing acenaphthene ring into the benzoxazine structure. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a benzoxazine resin containing an acenaphthene ring structure and a composition for a copper clad laminate.

[0005] In order to solve the above technical problems, the technical solution of the present invention is: a benzoxazine resin containing an acenaphthene ring structure and a composition for a copper clad laminate, wherein the innovation lies in that the composition is prepared by mixing and stirring 50 parts by mass of a benzoxazine resin containing an acenaphthene ring structure, 20 to 30 parts by mass of a DCPD epoxy resin, 10 to 20 parts by mass of a maleimide resin, 0.1 to 0.5 parts by mass of an imidazole catalyst, 60 to 80 parts by mass of a filler and 60 to 100 parts by mass of a solvent II at 30 to 50°C.

[0006] Furthermore, the benzoxazine resin containing an acenaphthene ring structure is prepared in the following manner: first, an acenaphthene compound and a phenolic compound containing a double bond are subjected to a polymerization reaction in the presence of a free radical initiator, an inhibitor, and a solvent I to obtain an oligomer solution, then, the solvent I in the solution is evaporated to obtain an oligomer containing an acenaphthene ring structure and a phenolic hydroxyl group, and finally, the oligomer is reacted with paraformaldehyde, an amine compound, and toluene at a certain temperature to obtain a benzoxazine resin containing an acenaphthene ring structure; The acenaphthylene compound is one or a mixture of two or more of acenaphthylene, 5-bromoacenaphthylene and dibromoacenaphthylene; The phenolic compound containing a double bond contains a phenolic hydroxyl group, a double bond and a benzene ring structure, and has a general chemical structure as shown in formula (1): In formula (1): R1 is any one of -CH=CH2, -CH2-CH=CH2, -C(=CH2)-CH3, -CH2-CH2-CH=CH2, -CH2-CH2=CH-CH2; R2 is H or -OCH3; The free radical initiator is one or a mixture of two or more of diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, dicyclohexyl peroxydicarbonate, isopropylbenzene hydroperoxide, and azobisisobutyronitrile; The polymerization inhibitor is one or a mixture of two or more of hydroquinone, p-tert-butylcatechol, 2,6-di-tert-butyl-p-methylphenol, p-benzoquinone, and 1,4-naphthoquinone; The solvent I is one or a mixture of two or more of methanol, ethanol, tetrahydrofuran, toluene, xylene, petroleum ether, butanone, and methyl isobutyl ketone; The oligomer containing an acenaphthene ring structure and a phenolic hydroxyl group has a general chemical structure as shown in formula (2): In formula (2), x is 1 to 5, y is 1 to 5, R3 and R4 are H and Br, R5 is -CH3, and R6 is , n=0, 1, 2, R7 is H, -OCH3; The weight average molecular weight of the oligomer containing acenaphthene ring structure and phenolic hydroxyl group is in the range of 200 to 2000; The paraformaldehyde is a mixture of one or more formaldehyde groups with a degree of polymerization of 10-100; The amine compound is one or a mixture of several of aniline, 3-vinylaniline, 2-allylaniline, 2-nitroaniline, 3-nitroaniline, 4-nitroaniline, 4-ethynylaniline and m-ethynylaniline; The catalyst is one or a mixture of zinc chloride, indium trihalide, ferric chloride, antimony pentachloride, trifluoromethanesulfonate, morpholine trifluoroacetate, aluminum trichloride-nitroalkyl complex metal halide; The benzoxazine resin containing an acenaphthene ring structure has a general chemical structure as shown in formula (3): In formula (3), x is 1 to 5, y is 1 to 5, R3 and R4 are H and Br, R5 is -CH3, and R6 is , n=0, 1, 2, R7 is H, -OCH3, R8 is H, -NO2, -CH=CH2, -CH2-CH=CH2, -C≡CH; The solid content of the composition is 58% to 75%; The DCPD epoxy resin has a general chemical structure as shown in formula (4):

[0007] The maleimide resin has a general chemical structure as shown in formula (5): In formula (5), R9, R 10 is one of -H, -CH3, -C2H5; The imidazole catalyst is one or a mixture of two or more of imidazole, 2-methylimidazole, 1-methylimidazole, 1,2-dimethylimidazole, 1,3-dimethylimidazole, and 2,4-dimethylimidazole; The filler is one or a mixture of two or more of montmorillonite, calcium carbonate, magnesium hydroxide, zinc borate, talc, aluminum hydroxide, kaolin, barium sulfate, silicon dioxide, silicon micropowder, mica powder, hollow glass microspheres, and fumed silica; The solvent II is one or a mixture of two or more of butanone, toluene, xylene, cyclohexanone, propylene glycol monomethyl ether, propylene glycol methyl ether acetate, N,N-dimethylformamide, N,N-dimethylacetamide, and methyl isobutyl ketone.

[0008] Furthermore, the preparation process of the oligomer containing acenaphthene ring structure and phenolic hydroxyl group is as follows: nitrogen is introduced into a reactor equipped with a stirrer, a thermometer, and a condenser, and 1 mol of acenaphthene compounds, 1 to 3 mol of phenolic compounds containing double bonds, 0.1 to 1% of a free radical initiator based on the total weight of the acenaphthene compounds and the phenolic compounds containing double bonds, 0.01 to 1% of a polymerization inhibitor based on the total weight of the acenaphthene compounds and the phenolic compounds containing double bonds, and solvent I twice the total weight of the acenaphthene compounds and the phenolic compounds containing double bonds are added, the temperature is raised to 70 to 100° C., and the reaction is carried out for 2 to 10 hours to obtain an oligomer solution containing acenaphthene ring structure and phenolic hydroxyl group, and the solvent I in the oligomer solution is evaporated under reduced pressure at this temperature to obtain an oligomer containing acenaphthene ring structure and phenolic hydroxyl group.

[0009] Furthermore, the preparation method of the benzoxazine resin containing an acenaphthene ring structure is as follows: in a reactor equipped with a stirrer, a thermometer, a condenser and a water separator, oligomers containing an acenaphthene ring structure and a phenolic hydroxyl group, an amine compound and polyformaldehyde in a molar ratio of 1:1.1-1.5:2.5-4 are added, and then toluene with a weight of 1-3 times the total mass of the mixture and a catalyst with a weight of 1‰-1% of the total weight of the material are added, and the temperature is raised after stirring evenly, and the water generated in the system is separated by a water separator while the temperature is raised. When the temperature rises to 110-130°C, the reaction is maintained for 2-5h, and the obtained resin is washed with a 1mol / L NaOH solution and layered, and the lower resin layer is removed, and then washed with deionized water and layered, and then the lower resin layer is removed, and toluene and water are removed by a rotary evaporator to obtain a benzoxazine resin containing an acenaphthene ring structure.

[0010] The advantages of the present invention are as follows: in the present invention, the benzoxazine resin containing the acenaphthene ring structure undergoes a free radical polymerization reaction between a double-bond phenolic compound and an acenaphthene compound to generate an oligomer containing a phenolic hydroxyl group, which is then reacted with paraformaldehyde and an amine compound to introduce the acenaphthene ring structure into the benzoxazine resin. By introducing the acenaphthene ring, the free volume of the benzoxazine resin is increased, and the dielectric constant and dielectric loss of the resin are reduced; at the same time, the biphenyl structure in the acenaphthene ring is used to improve the heat resistance of the product.

[0011] In the composition of the present invention, DCPD epoxy resin is introduced, because its structure contains non-polar dicyclopentadiene skeleton, which increases the free volume of molecules, so that the dielectric constant and dielectric loss of the product are further reduced; the maleimide resin with good structural symmetry and rigidity is introduced, so that the dielectric constant and dielectric loss of the product are further reduced; at the same time, due to the introduction of highly heat-resistant imide ring, the heat resistance of the product is further improved.

[0012] After the composition of the present invention is pressed into a plate: Tg≥230°C, Td5%≥390°C; dielectric constant≤3.5 (10GHz); dielectric loss≤0.008 (1OGHz); it has the characteristics of high peel strength, low dielectric constant, low dielectric loss, high glass transition temperature, etc., and can be used as a resin for high-performance copper clad laminates, suitable as a raw material for high-frequency and high-speed copper clad laminates, and can also be used in the fields of laminates, integrated circuit packaging, high-density Internet, etc.

[0013] The product of the invention has simple preparation process, good product performance and strong practicability. DETAILED DESCRIPTION

[0014] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation method, structure, characteristics and effects of the present invention are described in detail below in combination with the preferred embodiments.

[0015] The benzoxazine resin containing an acenaphthene ring structure and the composition for copper-clad laminates are prepared by uniformly mixing and stirring 50 parts by weight of the benzoxazine resin containing an acenaphthene ring structure, 20 to 30 parts by weight of a DCPD epoxy resin, 10 to 20 parts by weight of a maleimide resin, 0.1 to 0.5 parts by weight of an imidazole catalyst, 60 to 80 parts by weight of a filler and 60 to 100 parts by weight of a solvent II at 30 to 50°C.

[0016] The above-mentioned benzoxazine resin containing acenaphthene ring structure is prepared in the following manner: first, an acenaphthene compound and a phenolic compound containing a double bond are subjected to a polymerization reaction in the presence of a free radical initiator, an inhibitor, and a solvent I to obtain an oligomer solution; then, the solvent I in the solution is evaporated to obtain an oligomer containing an acenaphthene ring structure and a phenolic hydroxyl group; finally, the oligomer is reacted with polyformaldehyde, an amine compound, and toluene at a certain temperature to obtain a benzoxazine resin containing an acenaphthene ring structure.

[0017] The above-mentioned preparation process can be specifically divided into two steps: the first step is to prepare an oligomer containing an acenaphthene ring structure and a phenolic hydroxyl group: in a reactor equipped with a stirrer, a thermometer, and a condenser, nitrogen is introduced, and 1 mol of an acenaphthene compound, 1 to 3 mol of a phenolic compound containing a double bond, 0.1 to 1% of a free radical initiator based on the total weight of the acenaphthene compound and the phenolic compound containing a double bond, 0.01 to 1% of an inhibitor based on the total weight of the acenaphthene compound and the phenolic compound containing a double bond, and a solvent I twice the total weight of the acenaphthene compound and the phenolic compound containing a double bond are added, the temperature is raised to 70 to 100° C., and the reaction is carried out for 2 to 10 hours to obtain an oligomer solution containing an acenaphthene ring structure and a phenolic hydroxyl group, and the solvent I in the oligomer solution is evaporated under reduced pressure at this temperature to obtain an oligomer containing an acenaphthene ring structure and a phenolic hydroxyl group.

[0018] The second step is to prepare a benzoxazine resin containing an acenaphthene ring structure: in a reactor equipped with a stirrer, a thermometer, a condenser and a water separator, add oligomers containing an acenaphthene ring structure and a phenolic hydroxyl group, amine compounds and polyformaldehyde in a molar ratio of 1:1.1-1.5:2.5-4, wherein the oligomer is calculated based on the amount of phenolic hydroxyl group, and the amine compound is calculated based on the amount of amino group. Then, toluene with a weight of 1-3 times the total mass of the mixture and a catalyst with a weight of 1‰-1% of the total weight of the material are added, and the mixture is stirred evenly and heated. While heating, the water generated in the system is separated by a water separator. When the temperature rises to 110-130°C, the reaction is maintained for 2-5h, and the obtained resin is washed and layered with a 1mol / L NaOH solution, and the lower resin layer is removed, and then washed and layered with deionized water, and the lower resin layer is removed, and toluene and water are removed by a rotary evaporator to obtain a benzoxazine resin containing an acenaphthene ring structure.

[0019] In the above preparation, the acenaphthylene compound is one or a mixture of two or more of acenaphthylene, 5-bromoacenaphthylene and dibromoacenaphthylene.

[0020] The phenolic compound containing a double bond contains a phenolic hydroxyl group, a double bond and a benzene ring structure, and has a general chemical structure as shown in formula (1): In formula (1): R1 is any one of -CH=CH2, -CH2-CH=CH2, -C(=CH2)-CH3, -CH2-CH2-CH=CH2, -CH2-CH2=CH-CH2; R2 is H or -OCH3.

[0021] The free radical initiator is one of diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, dicyclohexyl peroxydicarbonate, isopropylbenzene hydroperoxide and azobisisobutyronitrile, or a mixture of two or more thereof.

[0022] The polymerization inhibitor is one or a mixture of two or more of hydroquinone, p-tert-butylcatechol, 2,6-di-tert-butyl-p-methylphenol, p-benzoquinone and 1,4-naphthoquinone.

[0023] Solvent I is one of methanol, ethanol, tetrahydrofuran, toluene, xylene, petroleum ether, butanone, methyl isobutyl ketone, or a mixture of two or more thereof.

[0024] The oligomer containing acenaphthene ring structure and phenolic hydroxyl group has the general chemical structure shown in formula (2): In formula (2), x is 1 to 5, y is 1 to 5, R3 and R4 are H and Br, R5 is -CH3, and R6 is , n=0, 1, 2, R7 is H, -OCH3.

[0025] The weight average molecular weight of the oligomer containing the acenaphthene ring structure and the phenolic hydroxyl group is in the range of 200 to 2000.

[0026] Paraformaldehyde is a mixture of one or more formaldehyde groups with a degree of polymerization of 10-100. The mole number is calculated according to the theoretical formaldehyde mole number, that is, mole number = mass × purity ÷ 30.

[0027] The amine compound is one or a mixture of several of aniline, 3-vinylaniline, 2-allylaniline, 2-nitroaniline, 3-nitroaniline, 4-nitroaniline, 4-ethynylaniline and m-ethynylaniline.

[0028] The catalyst is one or a mixture of zinc chloride, indium trihalide, ferric chloride, antimony pentachloride, trifluoromethanesulfonate, morpholine trifluoroacetate, aluminum trichloride-nitroalkyl complex metal halide.

[0029] The benzoxazine resin containing the acenaphthene ring structure has the general chemical structure shown in formula (3): In formula (3), x is 1 to 5, y is 1 to 5, R3 and R4 are H and Br, R5 is -CH3, and R6 is , n=0, 1, 2, R7 is H, -OCH3, R8 is H, -NO2, -CH=CH2, -CH2-CH=CH2, -C≡CH.

[0030] The solid content of the composition is 58% to 75%.

[0031] The DCPD epoxy resin is selected from one of DFE228 and DFE228H of Sichuan Dongcai Technology Group Co., Ltd. or a mixture of the two, and has a general chemical structure as shown in formula (4):

[0032] Maleimide resin has the general chemical structure shown in formula (5): In formula (5), R9, R 10 is one of -H, -CH3, -C2H5; The imidazole catalyst is one or a mixture of two or more of imidazole, 2-methylimidazole, 1-methylimidazole, 1,2-dimethylimidazole, 1,3-dimethylimidazole and 2,4-dimethylimidazole.

[0033] The filler is one or a mixture of two or more of montmorillonite, calcium carbonate, magnesium hydroxide, zinc borate, talc, aluminum hydroxide, kaolin, barium sulfate, silicon dioxide, silicon micropowder, mica powder, hollow glass microspheres, and fumed silica.

[0034] Solvent II is one or a mixture of two or more of butanone, toluene, xylene, cyclohexanone, propylene glycol monomethyl ether, propylene glycol methyl ether acetate, N,N-dimethylformamide, N,N-dimethylacetamide, and methyl isobutyl ketone.

[0035] Table 1 shows the dosage (unit: g) and process parameters for preparing oligomers containing acenaphthene ring structure and phenolic hydroxyl group:

[0036] Table 2 shows the raw material dosage (unit: g) and process parameters for preparing benzoxazine resin containing acenaphthene ring structure:

[0037] The paraformaldehyde used in Examples 2-1 to 2-4 was analytical grade granular paraformaldehyde from Merck Chemical with a purity of 95%.

[0038] Table 3 is a table of the dosage of the raw materials in the formula of the resin composition for copper clad laminates (unit: g):

[0039] Preparation of prepreg: Select a smooth and clean E-glass fiber cloth with a thickness of 0.2 mm, immerse it in the above composition (solution), take it out, and then bake it in an oven at 130-170°C for 4-7 minutes. The weight percentage of resin in the prepreg is 62%-68%.

[0040] Preparation of copper clad laminate: overlap the above-mentioned prepreg sheets, cover copper foil on both sides or one side of the prepreg sheets, and then place them in a hot press, maintain the heating rate at 1-3°C / min, and after reaching the temperature, press at 0.2-1MPa pressure and 80-150°C temperature for 1-3 hours, then continue to heat, maintain the heating rate at 1-3°C / min, and after reaching the temperature, press at 2-7MPa pressure and 180-250°C temperature for 1-6 hours. The RC of the board is 60±2%.

[0041] The technical performance comparison of the copper clad laminate pressed by the benzoxazine resin containing acenaphthene ring structure prepared by the present invention and the comparative example is shown in Table 4 below: Table 4: Technical performance of copper clad laminates pressed by benzoxazine resin compositions containing acenaphthene ring structures:

[0042] The technical performance test methods in Table 4 are as follows: (1) Dielectric constant The dielectric constant at 10 GHz was measured using the flat plate method according to 2.5.5.9 of IPC-TM-650.

[0043] (2) Dielectric loss factor tangent According to 2.5.5.9 of IPC-TM-650, use the flat plate method to measure the dielectric loss tangent at 10 GHz.

[0044] (3) Glass transition temperature (Tg) The measurement was performed by differential scanning calorimetry according to the DSC method specified in 2.4.25 of IPC-TM-650.

[0045] (4) Thermal decomposition temperature (Td) The test is carried out according to the method specified in 2.4.26 of IPC-TM-650.

[0046] As can be seen from Table 4, the board material obtained by applying the embodiment of the present invention has excellent heat resistance, low dielectric constant and dielectric loss factor. The composition of the present invention can be used in the fields of laminated boards, integrated circuit packaging, high-frequency and high-speed copper-clad boards, high-density Internet, artificial intelligence, etc., and has broad application prospects.

[0047] In the above embodiments: the percentages used, unless otherwise specified, are all mass (weight) percentages or percentages known to those skilled in the art; the proportions used, unless otherwise specified, are all mass (weight) proportions; and the weights may be in grams or kilograms.

[0048] In the above embodiments, the process parameters (temperature, time, pressure, etc.) in each step and the numerical values ​​of the amounts of each component are ranges, and any point can be applied.

[0049] The technical contents not specifically described in the present invention and the above embodiments are the same as the prior art, and the raw materials are all commercially available products.

[0050] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A benzoxazine resin containing an acenaphthene ring structure and a composition for a copper-clad laminate, characterized in that: The composition is prepared by uniformly mixing and stirring 50 parts by weight of a benzoxazine resin containing an acenaphthene ring structure, 20 to 30 parts by weight of a DCPD epoxy resin, 10 to 20 parts by weight of a maleimide resin, 0.1 to 0.5 parts by weight of an imidazole catalyst, 60 to 80 parts by weight of a filler and 60 to 100 parts by weight of a solvent II at 30 to 50°C.

2. The composition of benzoxazine resin and copper-clad laminate containing acenaphthene ring structure according to claim 1, characterized in that: The benzoxazine resin containing an acenaphthene ring structure is prepared in the following manner: first, an acenaphthene compound and a phenol compound containing a double bond are subjected to a polymerization reaction in the presence of a free radical initiator, an inhibitor, and a solvent I to obtain an oligomer solution, then, the solvent I in the solution is evaporated to obtain an oligomer containing an acenaphthene ring structure and a phenolic hydroxyl group, and finally, the oligomer is reacted with polyformaldehyde, an amine compound, and toluene at a certain temperature to obtain the benzoxazine resin containing an acenaphthene ring structure; The acenaphthylene compound is one or a mixture of two or more of acenaphthylene, 5-bromoacenaphthylene and dibromoacenaphthylene; The phenolic compound containing a double bond contains a phenolic hydroxyl group, a double bond and a benzene ring structure, and has a general chemical structure as shown in formula (1): (1) In formula (1): R1 is any one of -CH=CH2, -CH2-CH=CH2, -C(=CH2)-CH3, -CH2-CH2-CH=CH2, -CH2-CH2=CH-CH2; R2 is H or -OCH3; The free radical initiator is one or a mixture of two or more of diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl perbenzoate, dicyclohexyl peroxydicarbonate, isopropylbenzene hydroperoxide, and azobisisobutyronitrile; The polymerization inhibitor is one or a mixture of two or more of hydroquinone, p-tert-butylcatechol, 2,6-di-tert-butyl-p-methylphenol, p-benzoquinone, and 1,4-naphthoquinone; The solvent I is one or a mixture of two or more of methanol, ethanol, tetrahydrofuran, toluene, xylene, petroleum ether, butanone, and methyl isobutyl ketone; The oligomer containing an acenaphthene ring structure and a phenolic hydroxyl group has a general chemical structure as shown in formula (2): (2) In formula (2), x is 1 to 5, y is 1 to 5, R3 and R4 are H and Br, R5 is -CH3, and R6 is , n=0, 1, 2, R7 is H, -OCH3; The weight average molecular weight of the oligomer containing acenaphthene ring structure and phenolic hydroxyl group is in the range of 200 to 2000; The paraformaldehyde is a mixture of one or more formaldehyde groups with a degree of polymerization of 10-100; The amine compound is one or a mixture of several of aniline, 3-vinylaniline, 2-allylaniline, 2-nitroaniline, 3-nitroaniline, 4-nitroaniline, 4-ethynylaniline and m-ethynylaniline; The catalyst is one or a mixture of zinc chloride, indium trihalide, ferric chloride, antimony pentachloride, trifluoromethanesulfonate, morpholine trifluoroacetate, aluminum trichloride-nitroalkyl complex metal halide; The benzoxazine resin containing an acenaphthene ring structure has a general chemical structure as shown in formula (3): (3) In formula (3), x is 1 to 5, y is 1 to 5, R3 and R4 are H and Br, R5 is -CH3, and R6 is , n=0, 1, 2, R7 is H, -OCH3, R8 is H, -NO2, -CH=CH2, -CH2-CH=CH2, -C≡CH; The solid content of the composition is 58% to 75%; The DCPD epoxy resin has a general chemical structure as shown in formula (4): (4) The maleimide resin has a general chemical structure as shown in formula (5): (5) In formula (5), R9, R 10 is one of -H, -CH3, -C2H5; The imidazole catalyst is one or a mixture of two or more of imidazole, 2-methylimidazole, 1-methylimidazole, 1,2-dimethylimidazole, 1,3-dimethylimidazole, and 2,4-dimethylimidazole; The filler is one or a mixture of two or more of montmorillonite, calcium carbonate, magnesium hydroxide, zinc borate, talc, aluminum hydroxide, kaolin, barium sulfate, silicon dioxide, silicon micropowder, mica powder, hollow glass microspheres, and fumed silica; The solvent II is one or a mixture of two or more of butanone, toluene, xylene, cyclohexanone, propylene glycol monomethyl ether, propylene glycol methyl ether acetate, N,N-dimethylformamide, N,N-dimethylacetamide, and methyl isobutyl ketone.

3. The composition of benzoxazine resin and copper-clad laminate containing acenaphthene ring structure according to claim 2, characterized in that: The specific preparation process of the oligomer containing acenaphthene ring structure and phenolic hydroxyl group is as follows: nitrogen is introduced into a reactor equipped with a stirrer, a thermometer, and a condenser, 1 mol of acenaphthene compounds, 1 to 3 mol of phenolic compounds containing double bonds, 0.1 to 1% of a free radical initiator based on the total weight of the acenaphthene compounds and the phenolic compounds containing double bonds, 0.01 to 1% of a polymerization inhibitor based on the total weight of the acenaphthene compounds and the phenolic compounds containing double bonds, and solvent I twice the total weight of the acenaphthene compounds and the phenolic compounds containing double bonds are added, the temperature is raised to 70 to 100° C., and the reaction is carried out for 2 to 10 hours to obtain an oligomer solution containing acenaphthene ring structure and phenolic hydroxyl group, and the solvent I in the oligomer solution is evaporated under reduced pressure at this temperature to obtain an oligomer containing acenaphthene ring structure and phenolic hydroxyl group.

4. The composition of benzoxazine resin and copper-clad laminate containing acenaphthene ring structure according to claim 2, characterized in that: The preparation method of the benzoxazine resin containing an acenaphthene ring structure is as follows: in a reactor equipped with a stirrer, a thermometer, a condenser and a water separator, oligomers containing an acenaphthene ring structure and a phenolic hydroxyl group, amine compounds and polyformaldehyde in a molar ratio of 1:1.1-1.5:2.5-4 are added, and then toluene with a weight of 1-3 times the total weight of the mixture and a catalyst with a weight of 1‰-1% of the total weight of the material are added, and the mixture is stirred evenly and then heated, and the water generated in the system is separated by a water separator while the temperature is raised. When the temperature rises to 110-130°C, the reaction is maintained for 2-5h, and the obtained resin is washed with a 1mol / L NaOH solution, layered, and the lower resin layer is removed, and then washed with deionized water and layered, and then the lower resin layer is removed, and the toluene and water are removed by a rotary evaporator to obtain the benzoxazine resin containing an acenaphthene ring structure.

Citation Information

Patent Citations

  • N-semi aromatic hydrocarbyl diamine-bisphenol tetrafunctional fluorene-based benzoxazine and preparation method thereof

    CN103936686A

  • Flame-retardant high-heat-resistance low-dielectric benzoxazine resin and preparation method thereof

    CN113896850A